Gear tooth pitting modelling and detection based on transmission error measurements - Nabih Feki; Jérôme Cavoret; Fabrice Ville; Philippe Velex (European Journal of Computational Mechanics, 2013)
In this study, an experimental validation of a 3D gear dynamic model in the presence of localised faults such as pitting on tooth flanks is proposed. The corresponding numerical model accounts for spur and helical gear systems including gear errors and deviations along with the supporting shafts and bearings. Simulation results are compared with the evidence from a back-to-back test rig and the model validation relies on loaded transmission error (TE) measurements. Many numerical and experimental results on dynamic behaviours due to the presence of tooth pitting in geared systems are presented. Based on TE measurements, it is demonstrated that the actual vibrations generated by gear tooth pitting validate the gear model and its extension to consider such tooth surface failures.